Efektivitas Model Pembelajaran Problem Based Learning Terhadap Literasi Sains Siswa Pada Materi Klasifikasi Makhluk Hidup Kelas VII SMP - Andayani, Anindya Aulya; Agustina, Lina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in improving students’ scientific literacy. The research method used is pre-experimental with a one-group pretest-posttest design. The research sample consists of 32 seventh-grade students from class VII F, selected using purposive sampling techniques. Data collection techniques include a scientific literacy test conducted at the beginning and end of the study, supplemented by interviews with biology teachers regarding the implementation of the Problem-Based Learning model. The results of the study indicate a significant improvement in students’ scientific literacy after the implementation of the PBL model. The average pretest score of 64.72 (categorized as Moderate) increased to 83.25 (categorized as Very High) in the posttest. The distribution of scientific literacy improvement shows that 31.25% of students experienced a high increase, 59.38% a moderate increase, and 9.38% a low increase. These findings suggest that PBL enhances students’ understanding of scientific concepts, particularly in problem-solving and scientific data analysis. Thus, it can be concluded that Problem-Based Learning (PBL) is an effective teaching method for improving students’ scientific literacy.